2012
DOI: 10.1073/pnas.1120841109
|View full text |Cite
|
Sign up to set email alerts
|

Loss of DNA methylation affects the recombination landscape in Arabidopsis

Abstract: During sexual reproduction, one-half of the genetic material is deposited in gametes, and a complete set of chromosomes is restored upon fertilization. Reduction of the genetic information before gametogenesis occurs in meiosis, when cross-overs (COs) between homologous chromosomes secure an exchange of their genetic information. COs are not evenly distributed along chromosomes and are suppressed in chromosomal regions encompassing compact, hypermethylated centromeric and pericentromeric DNA. Therefore, it was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
140
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(152 citation statements)
references
References 53 publications
9
140
0
Order By: Relevance
“…3B). However, the presence of the heterochromatic knob on chromosome 4 in the Columbia accession, but not in other accessions, makes this result difficult to interpret (10).…”
Section: Suppression Of Pericentromeric Recombination Persists In Thementioning
confidence: 72%
See 1 more Smart Citation
“…3B). However, the presence of the heterochromatic knob on chromosome 4 in the Columbia accession, but not in other accessions, makes this result difficult to interpret (10).…”
Section: Suppression Of Pericentromeric Recombination Persists In Thementioning
confidence: 72%
“…Specifically, COs were reduced when the recombination interval was methylated on one homolog and were abolished almost completely when methylated on both homologs. In Arabidopsis, two recent mapping studies analyzed F 2 progeny derived from crosses between Columbia ddm1 and met1 [Col(ddm1),Col(met1)] DNA methylation mutants and wild-type Landsberg [Ler(WT)] accessions and showed that loss of DNA methylation could not alleviate the suppression of COs in pericentromeric regions of chromosomes (9,10). However, as pointed out by the authors, this experimental design could not rule out an inhibitory effect of sequence divergence between Col and Ler on COs.…”
mentioning
confidence: 99%
“…DNA methylation also represses CO formation (Maloisel and Rossignol 1998) and is sufficient to silence CO hotspots in Arabidopsis (Yelina et al 2015). CO distribution is largely modified in Arabidopsis met1 and ddm1 mutants, which show an increase of proximal recombination events and a simultaneous decrease in pericentromeric and distal regions (Colome-Tatche et al 2012;Melamed-Bessudo and Levy 2012;Mirouze et al 2012;Yelina et al 2012). Since H3K4me3 and H2A.Z landmarks are important for promotion of gene transcription (Liu et al 2009;Yelina et al 2012;Choi et al 2013) and are associated with high recombination rates in Arabidopsis (Yelina et al 2012) as well as in barley (Aliyeva-Schnorr et al 2015;Baker et al 2015), this suggests that both recombination and DNA-transposon insertion benefit from low compaction of DNA to occur within the genome.…”
Section: Retrotransposons Associate With Reduced Recombination Ratementioning
confidence: 99%
“…HR repairs DNA single-and doublestrand breaks, and the readily accessible regions of homology are required for its activity (Puchta 2005). Stresses that may change the chromatin structure either via changes in DNA methylation or histone modifications may also result in altered HR frequency (Bilichak et al 2012;Endo et al 2006;Gao et al 2012;Kirik et al 2006;Mirouze et al 2012).…”
Section: Introductionmentioning
confidence: 99%